Process‐Structure‐Formulation Interactions for Enhanced Sodium Ion Battery Development: A Review - Anne Sawhney (ChemPhysChem, 2022)
Before the viability of a cell formulation can be assessed for implementation in commercial sodium ion batteries, processes applied in cell production should be validated and optimized. This review summarizes the steps performed in constructing sodium ion (Na-ion) cells at research scale, highlighting parameters and techniques that are likely to impact measured cycling performance. Consistent process-structure-performance links have been established for typical lithium-ion (Li-ion) cells, which can guide hypotheses to test in Na-ion cells. Liquid electrolyte viscosity, sequence of mixing electrode slurries, rate of drying electrodes and cycling characteristics of formation were found critical to the reported capacity of laboratory cells. Based on the observed importance of processing to battery performance outcomes, the current focus on novel materials in Na-ion research should be balanced with deeper investigation into mechanistic changes of cell components during and after production, to better inform future designs of these promising batteries.